Operando pair distribution function analysis of nanocrystalline functional materials the case of TiO2-bronze nanocrystals in Li-ion battery electrodes - Karlsen, Martin A (Journal of applied crystallography, 2024)
© Martin A. Karlsen et al. 2024.